Clinicians’ Perspectives of Twice-Weekly Rivastigmine Patches for Alzheimer’s Disease Treatment in Spain: The VIITAL 2S Study - Piñol Ripoll, Gerard; Salas Carrillo, Mario (Patient preference and adherence, 2025)
Administration routes and dosage significantly impact Alzheimer's disease (AD) treatment effectiveness, as compliance in older patients depends on interactions between concomitant treatments, complex dosages, adverse effects, or medication tolerance. This study aims to describe patient and caregiver preferences concerning treatment with rivastigmine twice-weekly transdermal patches from the neurologists' and geriatricians' perspectives. VIITAL-2S was an ecological study based on aggregated data. A total of 250 Spanish neurologists and geriatricians answered a survey on the use, adherence, patient and caregiver satisfaction, and safety (skin tolerability) of twice-weekly rivastigmine patches. Most participating physicians reported having over 11 years of experience in their specialty. According to their responses, patients with AD attending Neurology and Geriatrics were usually in mild-moderate condition, and a mean of 61.4% received rivastigmine. Around 60% of patients lived with a family member, and over 80% had a caregiver, mainly their partner/spouse or other relative. Of note, more than half of patients attending Neurology and nearly 75% of patients in Geriatrics received 4-10 medications daily. Both specialists recommended the transdermal formulation to patients receiving rivastigmine. In 33.8% and 41.0% of patients receiving daily patches, neurologists and geriatricians, respectively, recommended switching to twice-weekly patches, considering higher administration comfort and caregiver preferences. Physicians reported high/very high satisfaction with twice-weekly patches in nearly 80% of patients. Comparing twice-weekly to daily patches, they observed higher comfort, more caregiver satisfaction, and enhanced adherence. Both specialists manifested preferring twice-weekly rivastigmine patches over daily ones, especially to increase caregivers' comfort, for patients without full-week caregiver support, and in cases of poor compliance with previous treatments. Neurologists and geriatricians consider the twice-weekly rivastigmine patch formulation beneficial for AD treatment in terms of treatment compliance, skin tolerability, satisfaction and comfort for patients and caregivers.